A rare case of Candida glabrata spondylodiscitis: case report and literature review. (March 2018) - Gagliano, Manfredi; Marchiani, Costanza; Bandini, Giulia; Bernardi, Paolo; Palagano, Nicolas; Cioni, Elisa; Finocchi, Martina; Bellando Randone, Silvia; Moggi Pignone, Alberto
Highlights: The incidence of spondylodiscitis is increasing due to the increase in susceptible population and improved ascertainment. The diagnosis is often delayed or missed. A fungal aetiology is rare. There is a global shift toward invasive candidiasis due to C. glabrata which has a variable susceptibility to antifungal drugs. Abstract: Background: Spondylodiscitis is an infection of the vertebral column, the incidence of which is increasing due to an increase in the susceptible population and improved ascertainment. This disease has been associated with a wide range of microorganisms. Fungal spondylodiscitis is uncommon (0.5–1.6%) and strongly associated with immunosuppression and diabetes (Gouliouris et al., 2010). A rare case of Candida glabrata spondylodiscitis in a non-neutropenic diabetic patient is reported herein, along with a review of the literature. Case report: A case of C. glabrata spondylodiscitis of L3–L4 metameres was diagnosed. The diagnosis was obtained through open biopsy of an abscess and culture examination. The patient was treated with anidulafungin and surgical debridement of the lesion. Conclusions: The diagnosis of spondylodiscitis is often delayed or missed. Physicians should consider this entity in the differential diagnosis of lumbar pain in order to initiate an appropriate therapy to prevent spinal cord lesions and disability. This is particularly relevant in the case of a fungal aetiology, as there is a recognized global shift towards invasive candidiasis due to non-albicans Candida species, in particular C. glabrata, which has variable susceptibility to antifungal drugs.